DYNAMIC ANALYSIS OF FPB ISOLATED BRIDGES BASED ON SIMPLIFIED MECHANICAL MODEL - LI Bing; WANG ShaoHua; DENG Bin (Jixie qiangdu)
Simplified mechanical model of FPB isolated bridges was established,the response amplitude was calculated used mode superposition method.The accuracy of results was verified by finite element simulation based on SAP2000.It was considered that the response amplitude agreed well with that of finite element simulation.Under the action of El Centro seismic wave,the results can meet engineering precision requirements basically.The response of girder and pier were mainly influenced by the isolated mode and second mode.